2021
DOI: 10.3390/w13030348
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mesophilic Anaerobic Digestion of Primary Sewage Sludge

Abstract: Processing of the produced primary and secondary sludge during sewage treatment is demanding and requires considerable resources. Most common practices suggest the cotreatment of primary and secondary sludge starting with thickening and anaerobic digestion. The aim of this study is to investigate the anaerobic digestion of the primary sludge only and estimate its impact on sludge treatment and energy recovery. Within this context, the performance of the anaerobic digestion of primary sludge is explored and foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Equation ( 8) calculates the thermal efficiency (η thermal-eng ) based on the ratio between the useful thermal power of the engine (TP useful-eng ) and the thermal power contained in biogas and consumed by the engine (TP biogas-eng ). Equation ( 9) estimates the energy efficiency (η energy-eng ), and Equation (10) estimates the usable thermal energy factor of the engine (UTEF) considering the thermal power that has application in the WWTP, that is, the power used (TP usable-eng ) against the value of the thermal power susceptible of application. Equation (11) estimates the work/heat ratio of engine (W/Q) eng , as the ratio between the mechanical power of the engine (MP eng ) and TP useful-eng :…”
Section: Engine Parameters and Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Equation ( 8) calculates the thermal efficiency (η thermal-eng ) based on the ratio between the useful thermal power of the engine (TP useful-eng ) and the thermal power contained in biogas and consumed by the engine (TP biogas-eng ). Equation ( 9) estimates the energy efficiency (η energy-eng ), and Equation (10) estimates the usable thermal energy factor of the engine (UTEF) considering the thermal power that has application in the WWTP, that is, the power used (TP usable-eng ) against the value of the thermal power susceptible of application. Equation (11) estimates the work/heat ratio of engine (W/Q) eng , as the ratio between the mechanical power of the engine (MP eng ) and TP useful-eng :…”
Section: Engine Parameters and Efficiencymentioning
confidence: 99%
“…UTEF = TP usabel−eng × 100/ TP useful−eng (10) (W/Q) eng = MP eng × 100/ TP useful−eng (11) Equation ( 12) estimates the ratio of the stoichiometric mass of air (A stoich ) for biogas combustion considering molar fraction of methane in biogas (X CH4 ) and the molecular weight of biogas and air (MW biogas , MW air ). Equation ( 13) estimates the stoichiometric ratio (F stoich ) for biogas-air:…”
Section: Engine Parameters and Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle this problem and increase the sustainability of conventional WWTPs a movement towards zero and/or negative net energy facilities (i.e., energy produced during treatment is greater than the energy required for their operation) should be made. Clean energy as set out in SDG 7 can be produced during wastewater treatment by technologies such as anaerobic digestion [4] and microbial fuel cells [5].…”
mentioning
confidence: 99%
“…Sakaveli et al [4] explored the anaerobic digestion of the primary, instead of the combined primary and secondary, sludge from a municipal WWTP and assessed its treatment and energy recovery potential. It was found that the overall yield in methane production during anaerobic digestion of primary sludge alone was higher (up to 40%) than that obtained by the anaerobic digestion of mixed primary and secondary sludge.…”
mentioning
confidence: 99%